Rupture point is associated with divergent hemodynamics in intracranial aneurysms - Hejčl, Aleš; Brunátová, Jana; Švihlová, Helena; Víteček, Jan; Wünschová, Andrea Vítečková; Sejkorová, Alena; Stratilová, Mária Hundža; Radovnický, Tomáš; Sameš, Martin; Hron, Jaroslav (Frontiers in Neurology, 2024)
Background Understanding the risk factors leading to intracranial aneurysm (IA) rupture have still not been fully clarified. They are vital for proper medical guidance of patients harboring unruptured IAs. Clarifying the hemodynamics associated with the point of rupture could help could provide useful information about some of the risk factors. Thus far, few studies have studied this issue with often diverging conclusions. Methods We identified a point of rupture in patients operated for an IAs during surgery, using a combination of preoperative computed tomography (CT) and computed tomography angiography (CTA). Hemodynamic parameters were calculated both for the aneurysm sac as a whole and the point of rupture. In two cases, the results of CFD were compared with those of the experiment using particle image velocimetry (PIV). Results We were able to identify 6 aneurysms with a well-demarcated point of rupture. In four aneurysms, the rupture point was near the vortex with low wall shear stress (WSS) and high oscillatory shear index (OSI). In one case, the rupture point was in the flow jet with high WSS. In the last case, the rupture point was in the significant bleb and no specific hemodynamic parameters were found. The CFD results were verified in the PIV part of the study. Conclusion Our study shows that different hemodynamic scenarios are associated with the site of IA rupture. The numerical simulations were confirmed by laboratory models. This study further supports the hypothesis that various pathological pathways may lead to aneurysm wall damage resulting in its rupture.